Powłoki Walcowe Zamknięć Wodnych - R. Dąbrowski (Engineering Transactions, 1962)
This is an analysis of the stress in the covering of steel water gates which may be treated as a circular cylindrical shell. After a brief discussion of various theories of such a shell (Sec. 1) further analysis is based on the Donnell differential equation. First, double series are used to solve the problem of a simply supported shell subjected to a hydrostatic pressure or a uniform radial load (Sec. 2). For shells of stronger curvature the convergence of the series is poor. In this case, a boundary value problem is solved, taking into consideration-the coefficient v ≠ 0. Equations for the internal forces are derived (Sec. 3).